Dye Removal from Aqueous Solution Using Egg Shell Powder - Azlinda, Abdul Ghani; Ragunathan, Santiagoo; Anbu Johnson, Dr.; Naimah, Ibrahim; Salsuwanda, Selamat (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.